SIÇAN BEYİN G PROTEİNLERİNİN KARAKTERİZASYONU - CABADAK, Hülya; KAN, Beki (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Heterotrimeric guanine nucleotide binding protein (G proteins) play a central role in regulation of signal transmission in the cell. G proteins which are localized in the inner surface of the cell membrane consist of α-, β- and γ- subunits. The α-subunit which binds guanine nucleotides (GTP and GDP) contains intrinsic GTPase activity. G proteins are divided into four families based on their α-subunits which confer their specifity: Gαs, Gαi, Gαq and Gα12. This study was designed to measure GTP binding activity and G protein expression in rat brain. Membrane extracts were prepared from whole brain and brain cortex. GTP binding activity in crude membrane fractions (P30) and membrane extracts (S142) was measured using [35S] GTPγS, the non-hydrolyzable analogue of GTP. Conclusion.- We observed that [35S] GTPγS binding increased with time and with increasing amounts of membrane proteins. We also demonstrated that GTPγS binding was strongly magnesium dependent and was maximum at 60mM MgCl2 concentration. The presence of G protein α and βγ subunits in whole brain and of Gαo and Gαi’ in brain cortex was shown by Western blot analysis.